2020
DOI: 10.1016/j.marpol.2019.103775
|View full text |Cite
|
Sign up to set email alerts
|

The illegal, unreported and unregulated fishing in Kuwait: Problems and solutions

Abstract: Kuwait is a country with an emerging economy that could benefit hugely from investment in its marine fisheries production.However, the country is constrained by several problems which affect the health of its coastal fish stocks. Illegal, unreported, and unregulated (IUU) fishing is the most serious of these problems because it reduces fish stock levels. In this study, we analyze IUU fishing in Kuwaiti waters, and assess its impact on fish stock levels and consequent damage to the marine economy and environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Fish stocks are declining in Kuwait, and the suggestion is that the main causes are overfishing, especially by illegal, unreported and unregulated (IUU) vessels, and pollution. We have dealt with overfishing elsewhere (Alqattan et al, 2020): this paper is about pollution. We should note, however, that both overfishing and pollution are immediate or proximate causes, and behind both lie deeper causes within the system of natural resource management in the country.…”
Section: Figure 1 |mentioning
confidence: 99%
See 1 more Smart Citation
“…Fish stocks are declining in Kuwait, and the suggestion is that the main causes are overfishing, especially by illegal, unreported and unregulated (IUU) vessels, and pollution. We have dealt with overfishing elsewhere (Alqattan et al, 2020): this paper is about pollution. We should note, however, that both overfishing and pollution are immediate or proximate causes, and behind both lie deeper causes within the system of natural resource management in the country.…”
Section: Figure 1 |mentioning
confidence: 99%
“…All of the fishers stated that they needed to travel to furtheraway locations in the high seas for those fish species because they can no longer find them near the coast because of the pollution. However, Alqattan et al (2020) showed that the abovementioned areas are being heavily fished by illegal fishing vessels, so pollution may not be the sole reason for the fish migration.…”
Section: The Effect Of Pollution On Fish Stocksmentioning
confidence: 99%
“…Unregulated Fishing refers to fishing activities carried out in areas where no applicable management measures exist." [4][5][6][7]. Figure 1 shows the common forms of IUU fishing.…”
Section: Introductionmentioning
confidence: 99%
“…IUU fishing can cause loss of economic revenue, environmental damage, and economic loss for coastal communities, and also it reduces fish stock levels [1,4,6,8,12]. IUU fishing also prevents governments and resource managers to gain the full economic rent from fisheries and disturbs the marine ecosystem sustainability [13].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to emphasize that a nation's strategic vision in the implementation of the Blue Economy must integrate coastal organizations to advance the sustainable management of marine ecosystems and resources [18], environmental concerns, habitat destruction, water pollution, eutrophication, biotic depletion, ecological effects, and disease outbreaks make it essential to incorporate new regulations. Stronger legislation that includes guidelines on the Blue Economy in the field of sustainable economic development could avoid socio-ecological conflicts with the population [16,[35][36][37][38].…”
mentioning
confidence: 99%